The - Khan, Roedad (Oxford University Press, 2002)
Confidential British diplomatic dispatches have surfaced that provide a revealing view of events in the subcontinent from 1947 right up to 1969. These documents, obtained from the British Archives, include reports of meetings with Heads of State and government, ministers, high dignitaries and political leaders, and critical analysis of the state of mind of the people in power and their political opponents. Also captured in these reports is the thinking and assessments of key players in the drama, the internal power struggle, shifting loyalties and Byzantine palace intrigues